Meningkatkan Keterampilan Event Orginizer Anggota Karang Taruna di Perumahan Hang Lekir Kecamatan Batam Kota - Angel Purwanti; Zakrimal Zakrimal; Ardhiya Annisa Ardhy; Dayanti Dayanti (Universitas Darussalam Gontor, 2019)
In era of globalization and free trade requires everyone to prepare reliable resources. Event Organizer (EO) is now more prospective. ’'The players' are not only many foreign competitors. This condition is a challenge for the Event Organizer, so that in view of the need for management maturity. Local Event Organizer has the potential to develop rapidly, considering that there are local, national and international events that require intelligent handling. In this service, the service team also connects communication and English skills that have very close relationships that benefit the community. Fostering an Event Organizer using English can provide benefits for youth in Youth.